Research Impact of Open Access Journals in Animal Sciences - Singh, Nirmal; Kumar, Dhiraj (Journal of Information and Knowledge, 2016)
The present study aims to examine the research impact of open access journals in the subject of animal sciences. The Impact Factor (IF) of journals, National Academy of Agricultural Sciences (NAAS) rating of journals, SCImago Journal Rank (SJR) and h-index are the parameters used to assess the research impact of periodicals enlisted in Directory of Open Access Journals (DOAJ) under the subject headings ’Animal Culture’ and ’Veterinary Medicine’. The findings revealed that more than 1/3rd of total 126 OA journals have succeeded to attain IF and NAAS rating. Despite this, only 6 of these journals have been able to find place in the core list of veterinary journals suggested by the Ohio State University. As large majority of journals got listed in DOAJ during 2011-2013, the research impact of OA has to be tested over the period.